Critical Thinking Skills Of MI Grade V Students Through The Application Of The Multiliteracy Learning Model - Safitri, Farah; Maufur, Syibli; Ummah, Inayatul (UIN Siber Syekh Nurjati Cirebon, 2024)
This study aims to determine how students' critical thinking skills through multiliteracy learning model. The approach used in this research is quantitative by using quasi-experimental method and the design used is non equivalent pre-test pos-test control group design. The population in this study was grade V Madrasah Ibtidaiyah students totaling 76 students. The sample used was 53 students divided into experimental classes totaling 33 students and control classes totaling 20 students. Data collection techniques used were observation of the application of multiliteracy learning models and tests used to measure students' critical thinking skills. The test used in the form of a description test totaling 7 questions with the criteria for questions from Bloom's taxonomy C4 to C6. The instruments in this study have been validated and declared valid. The analysis used is quantitative analysis. The data processed was obtained using normality test and hypothesis testing to determine the effect of multiliteracy learning model on students' critical thinking skills using SPSS 22 for windows. From the results of the study, it is known that the multiliteracy learning model in grade V Madrasah Ibtidaiyah based on the student's critical thinking skills test obtained an experimental pre-test mean of 63.03 and for the control pre-test mean of 61.60. While the mean result of the experimental post-test was 79.06 and for the control post-test mean was 73.00. This shows an increase in critical thinking skills of fifth grade students of Madrasah Ibtidaiyah. There is a significant effect of multiliteracy learning model on critical thinking skills of grade V students of Madrasah Ibtidaiyah based on hypothesis testing obtained Sig value. 0.022 <0.05 which means Ha is accepted, namely there is an effect of multiliteracy learning model on critical thinking skills of grade V students of Madrasah IbtidaiyahKeywords: Multiliteracy Learning Model, Critical Thinking Skills